The Accomplishment of community among small-scale fishers in Mercedes, Camarines Norte - Lamug, Corazon B. (2005)
Community-based action research and other intervention programs have gained
currency in such fields as forestry and natural resources. Many of these programs rely
on old conceptualizations of community focusing on such features as territorial
boundaries, common goals and even affective aspects. The paper offers an
ethnomethodological understanding of community as an accomplishment; it proposes
that the properties of social life which seem objective, factual and trans-situational,
are actually managed accomplishments or achievements of local processes. The aim
of the ethnomethodological inquiry is to analyze the situated conduct of fishers in
order to see how “objective” properties of community are accomplished.
Narratives of small scale fishers in Mercedes, Camarines Norte are analyzed to illustrate
how fishers are “doing community.” Because fishing involves access to resources in
the sea and competition among several fishers, the fishers have over time evolved a
set of norms governing conduct that is centered on sharing. The paper discusses
different categories of sharing – from negotiating access to marine resources to sharing
of catch with fishing companions and village people. Sharing also includes treating
friends and kin to drinks and food after a successful fishing event. Thus, sharing behavior
is something that is accomplished through interaction with others, and community is
an accomplishment involving the local management of fishers’ conduct in relation to
normative conceptions of appropriate attitudes and activities for particular fishing
related situations. It also cites implications of the use of the ethnomethodological
perspective on community for intervention programs specifically in forestry and
fisheries
Keywords: Small-scale fisheries; Sustainable fisheries; Small-scale fisheries -- environmental aspects